Intelligent 4D CT sequence scanning (i4DCT): Concept and performance evaluation. Issue 8 (23rd June 2019) - Werner, René; Sentker, Thilo; Madesta, Frederic; Gauer, Tobias; Hofmann, Christian
Abstract : Purpose: Four‐dimensional (4D) CT imaging is a central part of current treatment planning workflows in 4D radiotherapy (RT). However, clinical 4D CT image data often suffer from severe artifacts caused by insufficient projection data coverage due to the inability of current commercial 4D CT imaging protocols to adapt to breathing irregularity. We propose an intelligent sequence mode 4D CT imaging protocol (i4DCT) that builds on online breathing curve analysis and respiratory signal‐guided selection of beam on/off periods during scan time in order to fulfill projection data coverage requirements. i4DCT performance is evaluated and compared to standard clinical sequence mode 4D CT (seq4DCT) and spiral 4D CT (spiral4DCT) approaches. Methods: i4DCT consists of three main blocks: (a) an initial learning period to establish a patient‐specific reference breathing cycle representation for data‐driven i4DCT parameter selection, (b) online respiratory signal‐guided sequence mode scanning (i4DCT core), (c) rapid breathing record analysis and quality control after scanning to trigger potential local rescanning (i4DCT rescan). Based on a phase space representation of the patient's breathing signal, i4DCT core implements real‐time analysis of the signal to appropriately switch on and off projection data acquisition even during irregular breathing. Performance evaluation was based on 189 clinical breathing records acquired during spiral 4D CT scanning for RT planning (data acquisition period: 2013–2017; Siemens Somatom with Varian RPM system). For each breathing record, i4DCT, seq4DCT, and spiral4DCT scanning protocol variants were simulated. Evaluation measures were local projection data coverage β cov ; number ϵ total of local projection data coverage failures; and number ϵ pat of patients with coverage failures; average beam on time t beam on as a surrogate for imaging dose and total patient on table time t table as the time between first and last beam on signal. Results: Using i4DCT, mean inhalation and exhalation projection data coverage β cov increased significantly compared to standard spiral 4D CT scanning as applied for the original clinical data acquisition and conventional 4D CT sequence scanning modes. The improved projection data coverage translated into a reduction of coverage failures ϵ total by 89% without and 93% when allowing for a rescanning at up to five z ‐positions compared to spiral scanning and between 76% and 82% without and 85% and 89% with rescanning when compared to seq4DCT. Similar numbers were observed for ϵ pat . Simultaneously, i4DCT (without rescanning) reduced the beam on time on average by 3%–17% compared to standard spiral 4D CT. In turn, the patient on table time increased by between 35% and 66%. Allowing for rescanning led on average to additional 5.9 s beam on and 10.6 s patient on table time. Conclusions: i4DCT outperformed currently implemented clinical fixed beam on period 4D CT scanning approaches by means of a significantly smaller data coverage failure rate without requiring additional beam on time compared to, for example, conventional spiral 4D CT protocols. Abstract :